2015
DOI: 10.1590/s0080-623420150000500013
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress in elderly stroke survivors after hospital discharge to home

Abstract: Objective: To evaluate the relationship between perceived stress and comorbidities, neurological deficit, functional independence and depressive symptoms of stroke survivors after hospital discharge. Method: Cross-sectional study with 90 elderly stroke survivors. The National Institutes of Health Stroke Scale instrument, the Functional Independence Measure instrument, the Geriatric Depression Scale and the Perceived Stress Scale were used. Bivariate Pearson correlation, independent t test and multiple regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(47 citation statements)
references
References 22 publications
2
33
1
11
Order By: Relevance
“…In Portugal, a research with 47 elderlies of a Long-stay Institution found a score of 3.1 points (20) for the domain. When analyzing studies that applied the PSS in elderly in different contexts, the mean found was lower than that of a research conducted in the United States, 26.9 points (5) , and higher than that of two Brazilian studies that obtained mean of 18.5 points (6) and 14.0 points (21) . In Brazil, researchers used the PSS to assess the factors associated with perceived stress in 341 elderlies who provided care to elderlies in different contexts of dependence that resided in the community.…”
Section: Discussioncontrasting
confidence: 69%
“…In Portugal, a research with 47 elderlies of a Long-stay Institution found a score of 3.1 points (20) for the domain. When analyzing studies that applied the PSS in elderly in different contexts, the mean found was lower than that of a research conducted in the United States, 26.9 points (5) , and higher than that of two Brazilian studies that obtained mean of 18.5 points (6) and 14.0 points (21) . In Brazil, researchers used the PSS to assess the factors associated with perceived stress in 341 elderlies who provided care to elderlies in different contexts of dependence that resided in the community.…”
Section: Discussioncontrasting
confidence: 69%
“…With this in mind, it is extremely important to understand the evolution of this psychological stress and identify possible triggers and/or attenuators of psychological stress following a stroke, in order to enable the planning of interventions for effective stress management. Despite the great impact that psychological stress can cause on the life of a stroke survivor today, few researchers have dedicated themselves to investigating psychological stress and identifying its predictors among stroke survivors (Ostwald, Bernal, Cron, & Godwin, ; Ostwald, Swank, & Khan, ; Santos, Rodrigues, Marques, & Pontes‐Neto, ). Two cross‐sectional studies reported that a higher level of stress among stroke survivors was related to depression and lower functional independence after discharge (Ostwald et al, ; Santos et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great impact that psychological stress can cause on the life of a stroke survivor today, few researchers have dedicated themselves to investigating psychological stress and identifying its predictors among stroke survivors (Ostwald, Bernal, Cron, & Godwin, ; Ostwald, Swank, & Khan, ; Santos, Rodrigues, Marques, & Pontes‐Neto, ). Two cross‐sectional studies reported that a higher level of stress among stroke survivors was related to depression and lower functional independence after discharge (Ostwald et al, ; Santos et al, ). Ostwald et al () carried out a longitudinal study among stroke survivors to better understand stress changes and predictors and found that psychological stress decreased during the first year after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…As the participant reported, the reason might be that the participant performed the training tasks during mid-night when he was tired and felt frustrated on the tasks. Previous clinical findings have shown that higher perceived stress measured by PSS was associated with less functional independence in people with stroke (Santos et al, 2015). In addition, high-stress level assessed by psychological questionnaires has been shown to correlate with high stress-induced cortisol responses which increase medial temporal activity (Henckens et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…The psychometric properties of PSS have been confirmed (Lee, 2012). PSS has been used to assess perceived stress in people with stroke (Ostwald et al, 2008; Santos et al, 2015). The questions in PSS asked about participants' feelings and thoughts during the last month, and how often they felt a certain way.…”
Section: Introductionmentioning
confidence: 99%